Proceedings of the 29th ACM Symposium on Parallelism in Algorithms and Architectures 2017
DOI: 10.1145/3087556.3087564
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cover Time Bounds for the Coalescing-Branching Random Walk on Graphs

Abstract: We present improved bounds on the cover time of the coalescingbranching random walk process COBRA. The COBRA process, introduced in [Dutta et al., SPAA 2013], can be viewed as spreading a single item of information throughout an undirected graph in synchronised rounds. In each round, each vertex which has received the information in the previous round (possibly simultaneously from more than one neighbour and possibly not for the first time), 'pushes' the information to b randomly selected neighbours. The COBRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…This result improves the previous bounds of O n 2−1/d log n for d-regular graphs [27], and the recent O n 2 log n bound which however applies also to non-regular graphs [9]. Our bound is tight, as demonstrated by the example of an n-node graph obtained by two cliques of size n/2, by removing one of the edges in each clique, and adding two new edges between the cliques such that the graph remains regular.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…This result improves the previous bounds of O n 2−1/d log n for d-regular graphs [27], and the recent O n 2 log n bound which however applies also to non-regular graphs [9]. Our bound is tight, as demonstrated by the example of an n-node graph obtained by two cliques of size n/2, by removing one of the edges in each clique, and adding two new edges between the cliques such that the graph remains regular.…”
Section: Introductionsupporting
confidence: 86%
“…Cooper et al [8] showed that the cover time on d-regular graphs is bounded by O (1 − λ) −3 · log n w.h.p., where 1 − λ is the absolute spectral gap of the graph's random walk matrix. Very recently, Cooper et al [9] complemented this result by a…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The bound achieved by Reference [12] for expander graphs is optimal; for general graphs, our bounds and theirs are incomparable. In more recent results obtained subsequent to this article, Cooper et al [13] have obtained an improved O (n 2 log n) bound for cobra walks for general graphs and an improved bound for regular graphs in terms of the second eigenvalue of the graph.…”
Section: Our Results and Techniquesmentioning
confidence: 89%